Landscape Education: New Opportunities for Teaching and Research in Europe. Potentials of the LE:NOTRE ERASMUS Network for Landscape Architecture Education in Europe - Ellen Fetzer (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
In 2002, Eclas (the European Council of Landscape Architecture Schools) started the first Thematic Network Project in Landscape Architecture. Many databases on specialist literature, academic journals, European environmental policies, web links, landscape designs and so on, have been established. The LE:NOTRE thematic network meets the characteristics of a Community of Practice, a network of practitioners who share the same domain of interest. Learning in a CoP means a not traditional way of education, based on the contribution of all users and a lifelong learning. To develop this concept, some pilot courses have been organized in form of collaborative seminars whose participants, coming from different European universities, meet in a virtual room hosted by Le:Notre. A new concept of learning through communication and interaction in collaborative virtual environments is bore.